Fetoscopy and selective bipolar coagulation in a twin reversed arterial perfusion. A propos of the first case in Peru - Ventura Laveriano, Walter (2015)
A case of a pregnant woman referred to our center at 27 weeks of gestational age for twin reversed arterial perfusion (TRAP) sequence is reported. Fetoscopy and bipolar coagulation of the umbilical cord of the acardiac twin was performed with successful outcome.